1976
DOI: 10.1073/pnas.73.9.3035
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation in sickle cell hemoglobin solutions.

Abstract: The kinetic inhibition of the gelation of hemoglobin S is compared to the change in hemoglobin S solubility, when the so-ubility is altered by carbn monoxide, pH, or urea. By means of a new technique, the delay time and the extent of gelation are measured on the same sample. The delay time, td, is found to be proportional to a hig power (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) of the hemoglobin S solubility. Together with the previously reported concentration dependence, this result demonstrates that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(100 citation statements)
references
References 25 publications
(35 reference statements)
6
92
0
1
Order By: Relevance
“…Solubility is described as the concentration of deoxy Hb S present in the supernatant after fibers are allowed to form and sedimented by centrifugation. The ratio of initial concentration (C 0 ) to the soluble fraction (C s ) is known as the supersaturation ratio and can be expressed as: S ≡ C 0 /C s [54]. The solubility and the supersaturation ratio are a measure of the relative propensity of Hb molecules to form fibers.…”
Section: Equilibrium Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Solubility is described as the concentration of deoxy Hb S present in the supernatant after fibers are allowed to form and sedimented by centrifugation. The ratio of initial concentration (C 0 ) to the soluble fraction (C s ) is known as the supersaturation ratio and can be expressed as: S ≡ C 0 /C s [54]. The solubility and the supersaturation ratio are a measure of the relative propensity of Hb molecules to form fibers.…”
Section: Equilibrium Solubilitymentioning
confidence: 99%
“…Hb S 1.44 ± 0.14 1.11 ± 0.13 0.14 a S is the supersaturation ratio; S =(γ 0 C 0 )/(γ s C s ) [54]; γ values taken from Ross and Minton [44]. b i ⁎ is the size of the homogeneous nucleus; i ⁎ = −(4RT + δ 1 μ PC ) /RT ln S where δ 1 describes the fraction of intermolecular bonds in the nucleus relative to the infinite polymer, μ PC is the chemical potential contribution to the infinite polymer from the bonding free energy between molecules.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…A well known way to study such behavior is by sedimentation equilibrium 2; 3; 4 , in which the supernatant concentration reaches a saturating value of the solubility. Careful experiments showed that this concentration is independent of initial concentration, centrifugal force and duration (above a minimum concentration, force and time) 5 . This argued strongly in favor of this final concentration being a thermodynamic parameter, since it depended only on the conditions of the final state, not the path by which the final state was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…To understand why some proteins aggregate whereas others remain soluble, we recently observed that many proteins in the proteome are insufficiently soluble relative to their expression levels (24). Such proteins are metastable to aggregation as their concentrations exceed their solubilities, that is, they are supersaturated (24)(25)(26)(27). Upon formation of aggregate seeds by nucleation events, a supersaturated protein will form insoluble deposits until the concentration of its soluble fraction is reduced to match its solubility (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%